2017
DOI: 10.1186/s12879-017-2733-x
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology study of leptospirosis in febrile patients from Terai region of Nepal

Abstract: BackgroundLeptospirosis is a re-emerging zoonotic disease caused by pathogenic strains of bacteria belonging to genus Leptospira whose symptoms can range from mild clinical manifestations to a severe life threatening illness. This disease may be under-recognized in resource poor settings like Nepal where many clinical laboratories lack appropriate equipment, technology and personnel for proper diagnosis.MethodsWe used IgM ELISA to estimate the sero-prevalence of leptospirosis in a group of febrile patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 26 publications
6
15
5
Order By: Relevance
“…This is in harmony with findings from the Nepal study which also showed that persons in this age group are the active work force in the population, hence are more likely to get exposed during their various day-day jobs compared to others , [22,23]. Sixty-six percent of those that tested positive for the disease were female.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This is in harmony with findings from the Nepal study which also showed that persons in this age group are the active work force in the population, hence are more likely to get exposed during their various day-day jobs compared to others , [22,23]. Sixty-six percent of those that tested positive for the disease were female.…”
Section: Discussionsupporting
confidence: 84%
“…It is however much lower than the prevalence reported from the Terai region of Nepal [22]. The lower prevalence in our study could be as a result of the fact that we conducted our study between April and May when the rains were just starting as compared to the Nepal study, conducted during heavy rains and flooding [22]. Majority of the Leptospira-positive patients in this study were 25-40 years old.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Seropositive rate among the suspected cases of leptospirosis in central Terai and in Kathmandu has been reported at 4.8% and 28.6% [118,119], respectively. However, in western Terai, among the 144 febrile cases, 21% have been reported to be positive for leptospiral antibodies (IgM) indicating the acute leptospirosis [120]. Among the undiagnosed cases of acute encephalitis cases, 51.6% were positive and was higher in the age group of 6-15 years [121].…”
Section: Emerging Infectionsmentioning
confidence: 99%